LEGALITAS SURAT PENYERAHAN DENGAN GANTI RUGI YANG DIBUAT OLEH CAMAT SEBAGAI PENYELENGGARAAN URUSAN PEMERINTAHAN - IKA SATRIAWAN (LLPM Universitas Deli Sumatera, 2021)
The Camat, in addition to having attributive authority because of his position as the head of the sub-district, also has delegative authority. Delegation of authority in land services to district/city and sub-district and kelurahan regional governments is the district/city regional apparatus closest to the community, so the role of sub-districts in land services will increase. This type of research is normative legal research. The nature of this research is descriptive analytical. Data collection techniques in this study were carried out using library research methods. The results of the discussion in this study are the sub-district head in carrying out his duties gets the delegation of authority from and is responsible to the regent/mayor. Delegation of part of the authority of the Regent/Mayor to the Camat The delegation of government affairs from the Regent/Mayor to the Camat in the field of land affairs in the form of the authority of the regency/city government in the land sector. The Letter of Release of Rights with Compensation is written evidence recognized by the government (land office) as the basis for the right to submit an application for registration of land rights at the land office and also as evidence of a legal letter/written on physical control of land by one party. Keywords: Camat, Government and Release of Rights with Compensation